STRATEGI POSITIONING BATIK JAMBI MELALUI ATRIBUT PRODUK - jipranata jipranata; Johannes Johannes; Erida Erida (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
The purpose of this research is to examine consumer perception on some batik attribute: product quality, features, design and cost and their indicator. This perception is used to describe batik Jambi position. Research is belong to explanatory research where data is gathered by questionnaires. This research reveals to see the consumer perception of positioning batik Jambi with variables based on product quality, features, design and cost on which of these four variables is of twenty indicators. Methods used survey methods explanatory. Research finding showed that quality, feature, design, and cost that represent by twenty indicators is only significant represent by 10 indicators. Hence those significant indicators should be communicated to the customer to ensure that what customer found is provide by product.